The Campus Canopy, 1939-01-27 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1939)
The Campus Canopy, January 27, 1939. Vol. 5, No. 14. -- English Club To Sponsor Poet In Lecture On Wednesday -- Emory Junior Invites G.S.W.C. To Use Pool -- Kraft Demonstrates Recording At Chapel -- Canopy Holds First Meeting Of Series Monday -- New Coiffures, Styles Noted On Initiation Day -- Ivey Speaks In Jacksonville -- Far East And Mediterranean, Discussed By IRC -- Public Favorite No 1. Weds -- Geddy Speaks In Illustrated Lecture Saturday -- Girls Dance With The Glee Club
Georgia State Womans College Student Newspaper
Digitized from original print, Valdosta State University Archives and Special Collections, November 30, 2016.
Keywords: Valdosta State University -- Periodicals